Innovation management through the use of diversity networks. (18th December 2008) - Bednar, Peter; Welch, Christine; Katos, Vasilios
A methodology for innovation and analysis in a context of complex problem spaces is presented, introducing the idea of a diversity network. The methodology draws upon a framework which puts 'complexification' into systemic practice. Such an application helps individual participants to outline their narratives, create and agree upon categories, and use these to classify their narratives. Clusters of narratives, reflecting innovation through diversity networks of opinion and competences, are encouraged to emerge in analytical practice. This approach can be applied to promote creativity and sharing in a knowledge management context.